Reorganization of Knowledge and University: A Framework for a New Quest - Hediyetullah Aydeniz (İnsan & Toplum)
We live in an era in which, modern university with over the two centuries of its history is discussed a lot together with the globalization. The discussions on the establishment and institutionalization of modern university, which have attained its new position with nation state in the modern society (Scott 1990), and its functions in the modern society have reached a level where its raison d’etre is questioned. Whereas in Turkey, the university, as an organizational structure which is coeval with country’s modernization history, continues to be in the core of discussions. In this paper, I will study the university and reorganization of knowledge, paying close attention to the relationship between institutions that produce knowledge and structures that organize societies. The study is primarily concerned with the following questions: What is the status and structure of the university within the relationship of thought and social organization in modern society? What can be understood about institutionalization and the status of the university during Ottoman efforts towards modernization and within restructuring society in modern Turkey? Based on the above findings, how can we analyse the university and what are some new approaches to understanding the sociology of knowledge? In conclusion this study offers that the university and production of knowledge should be studied and analysed under the frame of reorganization of the society as a whole and on basis of four experiences which are of the modern west, of the ottoman modernization, of the Republic’s Turkey and of traditional institutions of higher education established previous era of modernization.